Productive Farming System in North-East India with special reference to Manipur - Sharma, Ph Ranjit; Devi, Th Renuka; Singh, R K Sandeep; Shyamananda, K; Singh, M Suraj (Indian Farming, 2021)
Under the Farmer FIRST Programme, Central Agricultural University, Imphal has identifiedtwo villages viz., Yairipok Top Chingtha and Yairipok Yambem of Imphal East district, ofManipur covering, a total of 600 farm families. However, farmers are well aware of cultivatingmajor Kharif and Rabi cereals, pulses, oilseeds and other major vegetables like cabbage, tomato,cauliflower, etc. The farming community, in general are marginal and small farmers. The 600farm families under FFP, CAU, Imphal were categorized as marginal - 593, Small- 4, Semi-Medium- 2, Medium- 1 and Large - 0 according to their size of land holding.